Aplikasi Web Registrasi Advertising Menggunakan Metode Paid-To-Promote - Rudi Prasetya; Danang Sutrisno (Teknik Informatika Universitas Pamulang, 2021)
The use of websites for advertising activities is rarely found in Indonesia. Most of the websites developed are still for commercial purposes and some are free but limit certain facilities. This study aims to develop a website that can facilitate these needs. The website that is built is a website that can be used to help display advertisements from advertisers and provide opportunities for people who want to help researchers in serving advertisements with certain benefits. The system will pay members who promote ads even if they only see the ad. Website development begins with designing a website database. The next stage is designing a website using a codeigniter framework. This web development model uses the concept of model, view, and controller (MVC) in codeigniter. Website model development is becoming faster and more structured. The results of this web design research are used for community social activities to earn income via the internet.